Plasmonic enhancement of visible light absorption in Ag-TiO2 based dye-sensitized solar cells - Gabriel Ayinde Alamu; Oluwaseun Adedokun; Ismaila Taiwo Bello; Yekinni Kolawole Sanusi (Chemical Physics Impact, 2021)
This work assessed the effect of plasmonic green synthesized silver nanoparticles (AgNPs) dispersed in Titanium dioxide (TiO2) nanoparticles on the efficiency of DSSC. Natural plant extracts from air-dried Neem (Azadirachta indica) and Henna (Lawsonia inermis) leaves were used as sensitizers with commercially available Ruthenium dye (N719). The optical absorption band obtained at 425 nm confirmed the presence of the AgNPs and incorporating the AgNPs into TiO2 and dye loading increased the absorbance significantly. The optical band gap results showed that the energy gap decreased as the absorbance increased. The DSSC sensitized by N719 dye offered the highest conversion efficiency of 4.09%, followed by 1.57% by Neem extract and 1.18% by Henna extract. It was shown from the results that natural plant extracts as sensitizers and plasmonic green synthesized AgNPs incorporated into TiO2 as the photoanode are good materials for the fabrication of DSSC with outstanding environmental friendliness.